Problems, control, and treatment of fat, oil, and grease (FOG): a review - Husain, Iman A. F.; Al-Khatib, Ma'an Fahmi Rashid; Jami, Mohammed Saedi; Mirghani, Mohamed Elwathig Saeed; Zainudin, Zaki; Hoda, Asif (Japan Oil Chemists' Society, 2014)
Presence of fat, oil, and grease (FOG) in wastewater is an ever-growing concern to municipalities and solid-waste facility operators. FOG enters the sewer system from restaurants, residences, and industrial food facilities. Its release into the sewer system results in a continuous build-up that causes eventual blockage of sewer pipes. Several researchers have investigated FOG deposition based on the local conditions of sewers and lifestyle. This paper attempts to review the physical and chemical characteristics of FOG, sources of FOG, and potential chemical and biological reactions of FOG. The effect of the aforementioned factors on the FOG-deposition mechanism is also discussed. Moreover, insight into the current control and treatment methods and potential reuse of FOG is highlighted. It is expected that this review would provide scientists and the concerned authorities a holistic view of the recent researches on FOG control, treatment, and reuse.